Adjoints and canonical forms of tree amplituhedra - Ranestad, Kristian; Sinn, Rainer; Telen, Simon (MATHEMATICA SCANDINAVICA, 2024)
We consider semi-algebraic subsets of the Grassmannian of lines in three-space called tree amplituhedra. These arise in the study of scattering amplitudes from particle physics. Our main result states that tree amplituhedra in Gr(2,4) are positive geometries. The numerator of their canonical form plays the role of the adjoint in Wachspress geometry, and is uniquely determined by explicit interpolation conditions.